1996
DOI: 10.1088/0022-3727/29/6/025
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of ion beam induced and atmospheric ageing of porous silicon using Al and caps

Abstract: Ion beam analysis data are presented on both freshly prepared and `aged' porous silicon layers of widely varying (10 - 85%) porosity. Both evaporated Al and PECVD surface capping layers are shown to suppress some of the rapid ion beam induced changes in chemical composition that have been reported during analysis of uncapped layers. Specifically, these capping layers were successful in eliminating carbon and oxygen accumulation within the material but they only slightly reduced hydrogen loss under ion bombard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 17 publications
4
8
3
Order By: Relevance
“…Two approaches can be considered: (1) physical protection of PSi by encapsulation (Giaddui et al 1996) or pore-filling techniques (Halimaoui et al 1995) and (2) changing the chemistry of the PSi surface. It may be useful to stabilize PSi without changing much of its original properties.…”
Section: Surface Chemical Modification Without Oxidationmentioning
confidence: 99%
“…Two approaches can be considered: (1) physical protection of PSi by encapsulation (Giaddui et al 1996) or pore-filling techniques (Halimaoui et al 1995) and (2) changing the chemistry of the PSi surface. It may be useful to stabilize PSi without changing much of its original properties.…”
Section: Surface Chemical Modification Without Oxidationmentioning
confidence: 99%
“…Thus, there is an interest in studying ageing under different conditions and in finding ways to prevent it happening. In previous work [9], it was reported that, under ion beam irradiation, the uptake of oxygen and carbon from a vacuum system increased as a function of the porosity of the material. It was also shown that thermally evaporated aluminium (Al) surface capping layers were effective in stopping the ion-beam-induced uptake of carbon and oxygen but had little effect on the loss of hydrogen.…”
Section: Introductionmentioning
confidence: 93%
“…Accelerator-based nuclear techniques were carried out on the 3 MV Dynamitron accelerator, the experimental procedure closely resembling that described in previous papers [2,9]. The elemental compositions (O, C and H) of the samples were also determined as described previously [2,9] using the computer code SIMS [10].…”
Section: Sample Preparation and Experimental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be useful to stabilize PSi without changing much its original properties. Basically, two approaches can be considered: (i) physical protection of PSi by encapsulation [87] or pore-filling techniques [88] and (ii) changing the chemistry of the PSi surface. Derivatization with long alkyl groups led to good stability of PL [89], EL [90], photonic properties [91], and biosensors [92].…”
Section: Stabilization Of the Porous Si Surfacementioning
confidence: 99%